2014
DOI: 10.1111/ced.12270
|View full text |Cite
|
Sign up to set email alerts
|

What's new in acne? An analysis of systematic reviews published in 2011-2012

Abstract: This review summarizes important clinical developments in acne vulgaris identified from 17 systematic reviews published between February 2011 and August 2012. Regarding causes, Demodex mites have been shown to be associated with both acne vulgaris and rosacea, although it is unclear if their eradication improves either disease. Some weak evidence has emerged that suggests a possible link between dairy produce and acne, which warrants further research. With reference to the effects of acne, there is good eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
1
27
1
1
Order By: Relevance
“…It is mainly considered an "adolescent" disorder and is characterized by spontaneous resolution in the late teens or early twenties in the majority of cases, in some of them with facial scar formation [2] . Prevalence of acne varies worldwide: studies published in the last decade reported prevalence ranging from 25.2%, among prepubertal children in Peru to 93.2 and 93.3% among adolescents in Iran and Australia [3] .…”
Section: Introductionmentioning
confidence: 99%
“…It is mainly considered an "adolescent" disorder and is characterized by spontaneous resolution in the late teens or early twenties in the majority of cases, in some of them with facial scar formation [2] . Prevalence of acne varies worldwide: studies published in the last decade reported prevalence ranging from 25.2%, among prepubertal children in Peru to 93.2 and 93.3% among adolescents in Iran and Australia [3] .…”
Section: Introductionmentioning
confidence: 99%
“…[344] However, they are not recommended as the first-line treatment for acne due to safety issues. [4455]…”
Section: Miscellaneous Agentsmentioning
confidence: 99%
“…Bowe et al [106] however considered there is reasonably compelling evidence that a highly glycemic diet may exacerbate acne, the role of ω-3 fatty acids, antioxidants, zinc and vitamin A being unclear. Finally, in a recent overview Bhate and Williams [107] insisted on the weakness of the evidence that suggests a possible link between dairy products and acne.…”
Section: Seborrhea and Acne: Inseparable Players Of The Pathogenic Prmentioning
confidence: 99%